DESIGN AND SELECTION OF PADDLE MATERIALS FOR HIGH-LEVEL ROWING COMPETITION APPLICATIONS USING MULTI-CRITERIA DECISION ANALYSIS - Nurfitrah, Aditya Eka; Riva Nanda, Iksan; Syahrial, Anne Zulfia (Universitas Mataram, 2025)
The study evaluated a variety of material alternatives including wood, bamboo, carbon fiber reinforced polymer (CFRP), and ceramics for use in high-performance paddleboard. The selection process considers factors such as strength, density, cost, and durability with a focus on the most relevant material criteria for the product. The weighted addition method is used to evaluate and rank several alternative materials that have been selected based on these criteria. Wood and bamboo are chosen for their sustainability, CFRP for their superior strength-to-weight ratio, and ceramics for their resistance to extreme conditions. The study found that CFRP had the highest score of around 85.40 due to its superior strength and lightweight. The framework proposed in this study could provide tools for rowing teams to optimize paddle materials so that they offer the potential for increased speed and performance in the competition. Â